TATA KELOLA PERUSAHAAN, KARAKTERISTIK PERUSAHAAN, AUDITOR SPESIALISASI INDUSTRI DAN MANAJEMEN LABA - Thiodora Alvino Efrata; Nicken Destriana (E-Jurnal Akuntansi TSM, 2021)
This study aims to obtain empirical evidence regarding the effect of independent variable on dependent variable. The sample was 134 firms obtained by purposive sampling method. The hypothesis was carried out by multiple regression analysis. The results for tenure of the chairman of audit committee, commissioners independent, managerial-ownership, leverage, firm size that its don’t have any influence on earnings management. Meanwhile, there is different result on industry specialized auditors which state that it has a positive effect on earnings management. This positive effect states that when a company was audited by auditor specialization industry, its affect company managers to do earnings management. This could be because the law in Indonesia relating to industrial specialization auditors is still weak, that earnings management practices may increase. Large KAP can help client companies to commit fraud in financial statements. There is a possibility that with Indonesia's weak law, cooperation occurs between industry specialized auditors dan client companies to carry out earnings management.